Model tata kelola dan supply chain sampah saat pandemi covid-19 di Kepulauan Seribu - Intan Yunianti Adiningsih; S Almayna; L E Silaban; R Afiana (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
Thousand Islands is one of the districts in Jakarta Capital Special Region, Indonesia. Thousand Islands has a different waste management to those on land, because the waste must be shipped by sea. The purpose of this study was to determine the management model and supply chain of waste in Thousand Islands by: (1) Analyzing the condition of waste in Thousand Islands during the Covid-19 pandemic, (2) Analyzing the waste supply chain in Thousand Islands during the Covid-19 pandemic, (3) Analyzing models and strategies for effective waste management and processing in Thousand Islands. The method used was descriptive analysis method, supply chain analysis method, and SWOT analysis method. The results of this study indicate that Thousand Islands already has good waste management which is indicated by the existence of various written policies and regulations from the government for waste management. However, there are several obstacles such as the limited amount of transportation to send waste and weather factors that sometimes hinder the delivery of waste to Bantar Gebang. The results of the SWOT analysis show that the condition of waste management in Thousand Islands is in quadrant I, its means the management supports an aggressive strategy.